2021
DOI: 10.1155/2021/2659550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed and Prognostic lncRNAs for the Construction of ceRNA Networks in Lung Adenocarcinoma

Abstract: Background. Long noncoding RNAs (lncRNAs) could function as competitive endogenous RNAs (ceRNAs) to competitively adsorb microRNAs (miRNAs), thereby regulating the expression of their target protein-coding mRNAs. In this study, we aim to identify more effective diagnostic and prognostic markers for lung adenocarcinoma (LUAD). Methods. We obtained differentially expressed lncRNAs (DElncRNAs), miRNAs (DEmiRNAs), and mRNAs (DEmRNAs) for LUAD by using The Cancer Genomes Atlas (TCGA) portal. Weighted gene coexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Liu et al demonstrated that downregulation of OGFRP1 inhibited the progression of NSCLC through miR-4640-5p/eIF5A axis (Liu X. et al, 2021). Furthermore, it has been reported that OGFRP1 is highly expressed in NSCLC tissues and significantly correlated with the prognosis of LUAD patients (Cui et al, 2021). As another core ferroptosis-related lncRNA noted in this study, APTR has been shown to reduce miR-132-3p and enhance YAP1 expression, which in turn promotes osteosarcoma progression (Guan et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Liu et al demonstrated that downregulation of OGFRP1 inhibited the progression of NSCLC through miR-4640-5p/eIF5A axis (Liu X. et al, 2021). Furthermore, it has been reported that OGFRP1 is highly expressed in NSCLC tissues and significantly correlated with the prognosis of LUAD patients (Cui et al, 2021). As another core ferroptosis-related lncRNA noted in this study, APTR has been shown to reduce miR-132-3p and enhance YAP1 expression, which in turn promotes osteosarcoma progression (Guan et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
“…The EMT process can thus be strongly induced in vivo by it (Song et al, 2018). Liu et al demonstrated that downregulation of OGFRP1 inhibited the progression of NSCLC through miR-4640-5p/eIF5A axis (Liu X. et al, 2021). Furthermore, it has been reported that OGFRP1 is highly expressed in NSCLC tissues and significantly correlated with the prognosis of LUAD patients (Cui et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cui's published work in Hindawi Journal of Oncology identified WWC2-AS2 as one of the lncRNAs involved in the construction of a Predictive long non-coding RNA (lncRNA) pattern in lung adenocarcinoma. [133][134][135][136] Lung Adenocarcinoma treatment:…”
Section: -110mentioning
confidence: 99%